ADGRE1 (EMR1, F4/80) Is a Rapidly-Evolving Gene Expressed in Mammalian Monocyte-Macrophages - Waddell, Lindsey A.; Lefevre, Lucas; Bush, Stephen J.; Raper, Anna; Young, Rachel; Lisowski, Zofia M.; McCulloch, Mary E. B.; Muriuki, Charity; Sauter, Kristin A.; Clark, Emily L.; Irvine, Katharine M.; Pridans, Clare; et al. (Frontiers in Immunology, 2018)
The F4/80 antigen, encoded by the Adgre1 locus, has been widely-used as a monocyte-macrophage marker in mice, but its value as a macrophage marker in other species is unclear, and has even been questioned. ADGRE1 is a seven transmembrane G protein-coupled receptor with an extracellular domain containing repeated Epidermal Growth Factor (EGF)-like calcium binding domains. Using a new monoclonal antibody, we demonstrated that ADGRE1 is a myeloid differentiation marker in pigs, absent from progenitors in bone marrow, highly-expressed in mature granulocytes, monocytes and tissue macrophages and induced by macrophage colony-stimulating factor (CSF1) treatment in vivo. Based upon these observations, we utilised RNA-Seq to assess the expression of ADGRE1 mRNA in bone marrow or monocyte-derived macrophages and alveolar macrophages from 8 mammalian species including pig, human, rat, sheep, goat, cow, water buffalo and horse. ADGRE1 mRNA was expressed by macrophages in each species, with inter-species variation both in expression level and response to lipopolysaccharide (LPS) stimulation. Analysis of the RNA-Seq data also revealed additional exons in several species compared to current Ensembl annotations. The ruminant species and horses appear to encode a complete duplication of the 7 EGF-like domains. In every species, Sashimi plots revealed evidence of exon skipping of the EGF-like domains, which are highly-variable between species and polymorphic in humans. Consistent with these expression patterns, key elements of the promoter and a putative enhancer are also conserved across all species. The rapid evolution of this molecule suggests a role in pathogen recognition.